Beleweniswêreld van die straatkind in Hillbrow - R. Hatting; M. Poggenpoel; C.P.H. Myburgh (AOSIS, 1998)
The street child that is driven by circumstances to live outside the supportive structure of the family, is on his own. He doesn't have the educational developmental opportunities that children who grow up in families and societies do. He finds himself in a unique educational and living environment. From an educational psychologist's point of view, this environment is abnormal. It is therefore a great challenge for the educational psychologist to try and avoid or resolve negative effects of the child's living environment. An exploratory-, descriptive-, contextual- and qualitative study was done, with the aim of gaining insight and understanding into the life of the street child in Hillbrow as well as his experiences of his situation. The results obtained from the interviews were placed in four categories. These categories are: The street child's continuous struggle to survive, his need for a "normal child life" , his inability to accept responsibility and the presence of a normative awareness within the street child. In conclusion it is clear that the experiential world of the street child is multi-facetted. In general it appears that the street child has many limitations and difficulties which he experiences, and that input by an educational psychologist can have meaningful influence in his life.